Role Of Anesthesia Technicians In Rapid Sequence Induction Preparedness (The Review of Diabetic Studies, 2025)
Rapid Sequence Induction (RSI) is a foundational, high-risk perioperative procedure designed to minimize the catastrophic risks of pulmonary aspiration of gastric contents and rapid arterial desaturation in patients with compromised airway reflexes or full stomachs. While historically conceptualized as a single-operator maneuver, contemporary perioperative medicine recognizes that safe airway management in emergency settings requires a highly coordinated, dual-practitioner team. This academic review examines the comprehensive, evidence-based role of the anesthesia technician—historically designated as the anesthetic assistant—in safeguarding patients during the periinduction period. Synthesizing literature, professional consensus guidelines, and human factors frameworks published prior to 2025, this paper analyzes the pathophysiological principles of airway protection and hypoxemia mitigation. It investigates the technician's technical responsibilities in preparing advanced airway equipment, executing specialized decontamination techniques such as Suction-Assisted Laryngoscopy and Airway Decontamination (SALAD), and managing complex pharmacological logistics. Furthermore, this report delineates the non-technical skills required for high-risk crisis resource management, highlighting the mechanics of cricoid pressure, the implementation of structured cognitive aids like the Vortex Approach, and the clinical utility of the "co-pilot" concept. Ultimately, standardized training paradigms, high-fidelity simulation, and robust institutional policies are recommended to integrate the anesthesia technician as an indispensable safety barrier in the operating theatre and non-operating room anesthesia locations.